The Notion of Eikos Within Conspiracy Theories. A Rhetorical Analysis. - Donckier de Donceel, Lucie (Rivista Italiana di Filosofia del Linguaggio, 2022)
Based on the analysis of one specific conspiracy theory, this paper will explore, from the rhetorical framework, the antic concept of likelihood [eikos]. Indeed, we believe that the rhetorical approach could allow us, on a larger scale, to (re)question, in the light of contemporary challenges, the complex relationship we have with the notions of rationality and truth. More precisely, to proceed with the rhetorical analysis, we will mobilise two types of logical reasoning: first, “the logic of the pot” argument from pragmatic logic and second, the logic of amplification and poetization of discourse. This will allow us to draw some comparisons between conspiracist speeches and, respectively, the rhetorical genres of judicial and epideictic discourses. The comparisons will be based on the criteria of likelihood, eikos, in order to propose a first definition of this notion in conspiracist discourses.